2006
DOI: 10.1373/clinchem.2005.057323
|View full text |Cite
|
Sign up to set email alerts
|

Coelution of Other Proteins with Albumin during Size-Exclusion HPLC: Implications for Analysis of Urinary Albumin

Abstract: Background: Size-exclusion HPLC has been used as an alternative to immunoassays for quantifying urinary albumin (microalbumin). Systematically higher values for the HPLC method have been proposed to result from nonimmunoreactive albumin. Methods: We evaluated separation of purified proteins and urinary components by size-exclusion HPLC using a Zorbax Bio Series GF-250 column eluted with phosphate-buffered saline. Urinary components eluting in the "albumin" peak were analyzed by mass spectrometry and reversed-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 43 publications
2
67
1
5
Order By: Relevance
“…When albumin does denature at extremely high temperature or pH, it aggregates irreversibly; this leads to precipitation of albumin rather than additional forms in solution (25 ). Some dimerization of albumin is observed with many preparations, including purified plasma albumin (21,25 ), but as in previously reported studies, we found albumin dimers to be minor components in urine. Aggregation of albumin with other components such as the Tamm-Horsfall protein would result in elution in size-exclusion chromatography as a much larger complex, and that has not been observed (15,21 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…When albumin does denature at extremely high temperature or pH, it aggregates irreversibly; this leads to precipitation of albumin rather than additional forms in solution (25 ). Some dimerization of albumin is observed with many preparations, including purified plasma albumin (21,25 ), but as in previously reported studies, we found albumin dimers to be minor components in urine. Aggregation of albumin with other components such as the Tamm-Horsfall protein would result in elution in size-exclusion chromatography as a much larger complex, and that has not been observed (15,21 ).…”
Section: Discussionsupporting
confidence: 88%
“…This bias has been hypothesized to result from modified forms of urinary albumin that are detected by the size-exclusion assay but not by immunoassays. Our laboratory, how-ever, determined that size-exclusion chromatography does not resolve albumin from a number of other urinary proteins and is an assay for a mixture of albuminsized molecules (ranging from about 40 000 to 80 000 Da) rather than an assay for albumin (21 ). This finding offers an alternative explanation for the difference between immunoassay and size-exclusion chromatography but does not completely rule out some contribution from modified forms of albumin with decreased immunoreactivity.…”
Section: © 2007 American Association For Clinical Chemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…This observation has lead to a controversial hypothesis that sizeexclusion chromatography detects a form of albumin that is not detected by immunoassay (114, 116 -118 ). This hypothesis has been questioned on the basis of the documented reactivity of polyclonal antisera with multiple antigenic sites in albumin (82,113 ). Moreover, the results of the size-exclusion method included other molecules of approximately the same size as albumin, including several urinary proteins (82 ).…”
Section: Current Routine Methods For Measuring Urine Albumin Routine mentioning
confidence: 99%
“…58 Its separation is based on differences in the sizes or weights of the analytes, which govern their access to the pore beads packed in a column. In general, the smaller analytes can enter the pores more easily and therefore spend more time in these pores, increasing their retention time.…”
Section: Size-exclusion Chromatographymentioning
confidence: 99%